2015
DOI: 10.1136/bmj.h1603
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive decompression versus open laminectomy for central stenosis of the lumbar spine: pragmatic comparative effectiveness study

Abstract: ObjeCtive To test the equivalence for clinical effectiveness between microdecompression and laminectomy in patients with central lumbar spinal stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
131
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(146 citation statements)
references
References 39 publications
4
131
1
5
Order By: Relevance
“…Another population‐based study from Scotland on patients with unruptured brain arteriovenous malformations showed that conservative management was associated with better clinical outcomes than treatment interventions (Salman et al., 2014). Using prospectively collected data from the Norwegian Registry for Spine Surgery, Nerland and coauthors were able to demonstrate that the effectiveness of laminectomy and microdecompression was equivalent in the management of lumbar spinal stenosis (Nerland et al., 2015). Another important aspect is that clinical registries and administrative databases allow inclusion of large patient groups that are ineligible for inclusion in randomized trials due to age and comorbidity (Giannadakis et al., 2016; Madsbu, Solberg, Salvesen, Nygaard, & Gulati, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another population‐based study from Scotland on patients with unruptured brain arteriovenous malformations showed that conservative management was associated with better clinical outcomes than treatment interventions (Salman et al., 2014). Using prospectively collected data from the Norwegian Registry for Spine Surgery, Nerland and coauthors were able to demonstrate that the effectiveness of laminectomy and microdecompression was equivalent in the management of lumbar spinal stenosis (Nerland et al., 2015). Another important aspect is that clinical registries and administrative databases allow inclusion of large patient groups that are ineligible for inclusion in randomized trials due to age and comorbidity (Giannadakis et al., 2016; Madsbu, Solberg, Salvesen, Nygaard, & Gulati, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nerland and colleagues' study compares the ''traditional'' surgical treatment for spinal stenosis, open laminectomy, with a newer and less invasive alternative technique, thē microdecompression [4]. Patients with a central stenosis of the lumbar spine at one or two lumbar levels underwent either an open laminectomy with resection of the spinous process, laminas and medial aspects of the facet joints, or a microdecompression.…”
Section: Open Laminectomy Versus Microdecompressionmentioning
confidence: 99%
“…Widespread adoption of these techniques should always be preceded by careful evaluation to ensure safety and determine added value of such so-called surgical innovation [2,3]. Actual and controversial topics concerning MIS for lumbar spinal stenosis (LSS) were recently addressed in high-quality studies: open laminectomy versus microdecompression by Nerland et al and decompression versus interspinous process implant by our group [4,5]. In some way, the opposite of MIS was addressed in a recent landmark study by Försth et al; does decompression versus decompression plus instrumented fusion for LSS yield better outcomes [6]?…”
mentioning
confidence: 99%
“…Microinstability has clinical relevance and may be helpful to distinguish patients who require decompression alone from those who require decompression plus fixation [1]. Giannadakis et al reported low complication rates in microsurgical decompression for central lumbar stenosis in patients without radiological instability; however, an equivalent outcome was previously demonstrated in microsurgical decompression or laminectomy [4]. It would be interesting to assess microsurgical decompression in patients affected by microinstability, since in these patients a standard laminectomy may aggravate the instability, and fixation is probably too aggressive a treatment.…”
mentioning
confidence: 99%